2021
DOI: 10.1080/14772019.2021.1924301
|View full text |Cite
|
Sign up to set email alerts
|

New earliest Paleocene (Puercan) periptychid ‘condylarths’ from the Great Divide Basin, Wyoming, USA

Abstract: An earliest Paleocene (Puercan) locality in the China Butte Member of the Fort Union Formation in the Great Divide Basin (GDB) of Wyoming contains a diverse mammalian faunal assemblage, including a number of 'condylarth' taxa. From UCM locality 2011035, we describe three new periptychid 'condylarths' and report first occurrences of Maiorana noctiluca, Ampliconus antoni and Conacodon harbourae from the GDB. The new genus and species Miniconus jeanninae is characterized by a ridge-like metaconid and incipient pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The early diversification of bats may be linked to the ecological opportunity afforded by niches vacated by the extinction of non-avian dinosaurs (Madelaine & Atteberry, 2021). Although early fossils are lacking, it has been suggested that ancestral bats in the Paleogene resembled terrestrial small-bodied insectivores (Gill et al, 2014;Madelaine & Atteberry, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The early diversification of bats may be linked to the ecological opportunity afforded by niches vacated by the extinction of non-avian dinosaurs (Madelaine & Atteberry, 2021). Although early fossils are lacking, it has been suggested that ancestral bats in the Paleogene resembled terrestrial small-bodied insectivores (Gill et al, 2014;Madelaine & Atteberry, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the greater taxonomic richness and evenness of the Littleton local fauna relative to more northern and eastern local faunas such as Luck O Hutch could relate to latitudinal and/or paleoenvironmental differences as well. The high richness of archaic ungulates in the Pu1 local fauna of the Great Divide Basin in Wyoming might also reflect a closer proximity to upland environments (Atteberry & Eberle, 2021; McComas & Eberle, 2016). That said, we underscore that these faunas have wide age brackets that might give a false sense of contemporaneity.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the generic and specific constituents of the periptychid subgroups-Periptychinae, Anisonchinae, Conacodontinae-have fluctuated substantially (e.g., Archibald et al 1983a, b), with some likely being paraphyletic (e.g., Anisonchinae; Archibald 1993Archibald , 1998Shelley 2018). Further, recent phylogenetic hypotheses propose that Mimatuta and Maiorana, two genera traditionally considered basal periptychids (Van Valen 1978;Archibald 1998), do not belong in the Periptychidae (Shelley 2018;Atteberry and Eberle 2021), raising questions about periptychid character polarity and evolutionary trends.…”
Section: Introductionmentioning
confidence: 99%
“…Note the high species richness of periptychids relative to all other eutherian families. Species richness data were compiled from Lofgren et al (2004), Silviria (2019), Atteberry and Eberle (2021), and Wilson Mantilla et al (2021). Note that the white portion between Purgatoriidae and Taeniodonta represents the putative carnivoran Ravenictis krausei, Arctocyonidae includes taxa (e.g., Carcinodon) that were previously considered oxyclaenids (see Williamson and Carr 2007), and taxa included in the Mioclaenidae and Apheliscidae have been variously referred to the Hyopsodontidae (see Zack et al 2005 andWeil 2011).…”
Section: Introductionmentioning
confidence: 99%